Black swan -or- black boxed economics: applying ontology, Keynesianism, and constructivism to policy and market analysis. Issue 5 (3rd September 2022) - Hernandez, Christian
ABSTRACT: What are black swans? And why are mainstream economists so often surprised by financial crises? Furthermore, have supply-side responses to crises merely deepened economic inequality and instability? Rather than simply comparing theories and methods – economics' 'ontological turn' posits that what is foremostly required is an audit of prevailing theories' metaphysical commitments. That is, to interrogate what economics presumes there is to observe, interact with, and know. Seeking to garner greater analytical purchase over the 'real-world', the ontological turn has also birthed several multidisciplinary syntheses – namely, Austrian-materialism (Lewis, P., 2005. Boettke, the Austrian school and the reclamation of reality in modern economics. The Review of Austrian Economics, 18 (1), 83–108.) and Keynesian-critical realism (Lawson, T., 2003. Reorienting economics . New York: Routledge.). Alternatively, and in support of the constructivist claim that social dynamics ultimately drive economics, this paper resituates and extends Wesley Widmaier's (2004) vision of a Keynesian-constructivism within the broader ontological turn. Herein, this paper interrogates the concepts of black swans vis-à-vis post-Keynesian understandings of business cycles, demand-side logics, and Modern Money – en route to establishing new analytical frameworks.